To the letter : a celebration of the lost art of letter writing - Garfield, Simon (Gotham, 2013)
An ode to the dwindling art of letter writing explores its potential salvation in the digital age, chronicling the history of letter writing as reflected by love letters, chain mail, and business correspondence, while surveying the role that letters have played as literary devices.